Immunogenicity and protective efficacy of the HC009 mRNA vaccine against SARS-CoV-2 - Liu, Juan; Han, Huafeng; Yang, Binbin; Zhang, Naifang; Li, Jing; Chen, Xicheng; Wu, Jie; Zhao, Yingying; Yang, Yongsheng (Frontiers in Immunology, 2024)
With the rapid global spread of COVID-19 and the continuous emergence of variants, there is an urgent need to develop safe and effective vaccines. Here, we developed a novel mRNA vaccine, HC009, based on new formulation by the QTsome delivery platform. Immunogenicity results showed that the prime-boost immunization strategy with HC009 was able to induce robust and durable humoral immunity, as well as Th1-biased cellular responses in rodents or non-human primates (NHPs). After further challenge with live SARS-CoV-2 virus, HC009 provided adequate protection against virus infection in hACE2 transgenic mice. Therefore, HC009 could provide significant immune protection against SARS-CoV-2.